APICAL DEBRIS EXTRUSION DURING INSTRUMENTATION WITH CONTINUOUS AND RECIPROCATING SYSTEMS - Dadalti, Manoela Teixeira de Sant'Anna (2021)
Objective: to evaluate the amount of apical debris extrusion during root canal preparation using continuous and reciprocating systems. Material and Methods: Forty lower incisors were selected and randomly divided into four groups (n=10) for root canal preparation. Two multifile systems with continuous rotation (iRace®and Mtwo®) and two reciprocating single-file systems (Reciproc® and WaveOne®) were used. In the iRace® group, the R1 (15/.06), R2 (25/.04) and R3 (30/.04) instruments were used. In the Mtwo® group, the 10/.04, 15/.05, 20/.06, and 25/.06 instruments were used. In the Reciproc® and WaveOne® groups, the R25 and 25/.04 instruments were used, respectively. Apical debris extrusion was determined by calculating the difference between the pre- and post-instrumentation weight of the Eppendorf tubes. Statistical analysis was performed using the analysis of variance (ANOVA) test with the Bonferroni correction (p<0.05). Results: The iRace® group demonstrated significantly more apical extrusion than the Reciproc® group (p<0.05). There was no statistically significant difference between the Mtwo®, Reciproc®, and WaveOne® groups (p>0.05). Conclusion: All of the evaluated systems produced apical debris extrusion. The iRace® system produced more apical debris extrusion than the Reciproc® system, and there was no difference observed in this regardbetween the Mtwo®, Reciproc®, and WaveOne® systems.